2022
DOI: 10.3389/fpls.2022.802801
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Characterization and Untargeted Metabolomics of Oyster Mushroom Produced Using Astragalus membranaceus var. mongolicus Stems and Leaves as Substrates

Abstract: Astragalus membranaceus var. mongolicus (AMM) is an edible and medicinal material and is commonly used in East Asia. According to the pharmacopeia of China, the dried root of AMM is medicinal. However, the aerial parts of AMM are always directly discarded after harvest. The stems and leaves are also rich in active compounds, including saponins, flavonoids, terpenoids, and polysaccharides. To rationally use resources, waste products from AMM stems and leaves are useful substrates for edible fungus cultivation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Our previous study reported similar findings ( Zeng et al., 2022b ). In the case of C. pilosula , the content of lobetyolin in the agro-waste residues (dried stems and leave) were 0.142 ± 0.011 mg/g (0.0142%).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Our previous study reported similar findings ( Zeng et al., 2022b ). In the case of C. pilosula , the content of lobetyolin in the agro-waste residues (dried stems and leave) were 0.142 ± 0.011 mg/g (0.0142%).…”
Section: Resultssupporting
confidence: 85%
“…Referring to the method recorded in previous studies ( Ma et al., 2021 ; Zeng et al., 2022b ), six biological replicates of mushrooms from CSL and control group were assayed for sample extraction and metabolomics analysis. In brief, 50 mg of each sample was extracted with a methanol buffer with internal standard (0.4 mL 80% aqueous, and 20 μL 0.3 mg/mL 2-chloro-D-phenylalanine) for 30 min in an ultrasonic bath.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is used as medicine and food in the improvement of health and treatment of various disease [16]. Various scientific literatures show that the supplementation of the mushroom-growing substrates with herbs have simultaneous edible and medicinal value, such as Astragalus and Codonopsis pilosula enhancing the nutritional value of edible fungi [14,17,18]. Hengshan Astragalus (also known as "Zheng Bei Qi", meaning Astragalus of geo-authentic origin), which is produced on Hengshan Mountain, Hunyuan County, Shanxi Province, is a widely used traditional Chinese herb and nutraceutical [19].…”
Section: Introductionmentioning
confidence: 99%